MScanFit motor unit number estimation of abductor pollicis brevis: Findings from different experimental parameters - Zong, Ya; Lu, Zhiyuan; Xu, Peipei; Chen, Maoqi; Deng, Lianfu; Li, Sheng; Zhang, Yingchun; Xie, Qing; Zhou, Ping (Frontiers in Aging Neuroscience, 2022)
MScanFit motor unit number estimation (MUNE) based on the recording of the compound muscle action potential (CMAP) scan has wide applications. This study evaluated the effect of different CMAP scan settings on MScanFit MUNE. CMAP scan of the abductor pollicis brevis (APB) muscle was performed in 10 healthy subjects at a United States (US) research center using different stimulus pulse widths (0.1, 0.2 ms) and total number of stimuli or steps (500, 1,000), and in 12 healthy subjects at a China research center using a 0.1 ms pulse width and 500 steps. MScanFit MUNE was derived using the default model parameters. A significantly higher MUNE was obtained using the shorter than longer pulse width; 84.70 ± 21.56 (500 steps) and 77.90 ± 27.62 (1,000 steps) at a pulse width of 0.1 ms vs. 67.60 ± 18.72 (500 steps) and 62.20 ± 15.82 (1,000 steps) at a pulse width of 0.2 ms (p < 0.05). However, MUNE was unrelated to the number of steps (500 vs. 1,000, p > 0.1). MUNE was significantly higher in persons studied in the China center (136.42 ± 32.46) than the US center (84.70 ± 21.56) despite each center using the same pulse widths and steps (p < 0.001). After excluding the ethnicity, age and experimenter factors, this significant difference is speculated to be partly related to different electrode size used in the two centers. The findings suggest that CMAP scan experimental parameters should remain consistent, so the MScanFit MUNE will not be compromised by non-physiological factors.